Pengaruh Pelatihan Kerja dan Fasilitas Kesejahteraan Terhadap Produktivitas Karyawan Pada PT. KAI Divre IV Tanjung Karang - Dhini Dwi Cahyani; Muhammad Yusuf Sulfarano Barusman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The purpose of this study is to examine how employee productivity at PT Kereta Api Indonesia (Persero) Regional Division IV Tanjung Karang is affected by welfare amenities and job training. The increasing demands for organizational efficiency and the rise in passenger volume, which necessitate higher levels of human resource productivity, are the background of this study. Nonetheless, a number of issues remain, including the discrepancy between job requirements and training materials, as well as disparities in how employees view the company's welfare facilities. This study uses a correlational research design and a quantitative methodology. 2,087 employees make up the population, and 95 respondents, calculated using the Slovin formula with a 10% margin of error, make up the sample. Random sampling is the method of sampling that is employed. Likert scale questionnaires were used to gather data, and multiple linear regression analysis was performed with the aid of SPSS software. The findings demonstrate that welfare programs and job training both significantly and favorably impact worker productivity. At the same time, production is significantly impacted by both factors. With a coefficient of determination (R2) of 56.1%, job training and welfare facilities account for 56.1% of employee productivity, with other factors not included in this study influencing the remaining 43.9%. In conclusion, PT KAI Regional Division IV Tanjung Karang's employee productivity is greatly enhanced by pertinent work training and sufficient welfare amenities.